2018
DOI: 10.1038/s41598-018-31853-0
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 is required for the proliferation of osteoblast progenitors and induces proliferation by regulating Fgfr2 and Fgfr3

Abstract: Runx2 and Sp7 are essential transcription factors for osteoblast differentiation. However, the molecular mechanisms responsible for the proliferation of osteoblast progenitors remain unclear. The early onset of Runx2 expression caused limb defects through the Fgfr1–3 regulation by Runx2. To investigate the physiological role of Runx2 in the regulation of Fgfr1–3, we compared osteoblast progenitors in Sp7−/− and Runx2−/− mice. Osteoblast progenitors accumulated and actively proliferated in calvariae and mandibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 60 publications
2
109
1
Order By: Relevance
“…Therefore, we speculated that appropriate cyclic pressure may promote the osteogenic differentiation in hPDLCs. Combined with the researches that RUNX2 also associated with cell proliferation and could not be used to indicated the role on osteogenic differentiation by itself [28,29]. In the present study, we also detect the expression level of OCN, OPN and OSX, who were regarded as the markers in the maturity of osteoblast and bone mineralization to verify the osteogenic differentiation of hPDLCs after dynamic cyclic stress during LPS-induced inflammation [30,31].…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, we speculated that appropriate cyclic pressure may promote the osteogenic differentiation in hPDLCs. Combined with the researches that RUNX2 also associated with cell proliferation and could not be used to indicated the role on osteogenic differentiation by itself [28,29]. In the present study, we also detect the expression level of OCN, OPN and OSX, who were regarded as the markers in the maturity of osteoblast and bone mineralization to verify the osteogenic differentiation of hPDLCs after dynamic cyclic stress during LPS-induced inflammation [30,31].…”
Section: Discussionmentioning
confidence: 68%
“…FGF induces the proliferation of osteoblast lineage cells and increases bone formation in vivo, but inhibits osteoblast differentiation in vitro, while gain-offunction mutations in the FGFR1, FGFR2, and FGFR3 genes cause a number of craniosynostosis syndromes, such as Apert, Crouzon, Pfeiffer, and Muenke syndromes as well as Thanatophoric dysplasia (12,13,32). We also recently reported that Runx2 enhanced the proliferation of osteoblast progenitors through the direct regulation of Fgfr2 and Fgfr3 (33). Canonical Wnt signaling is essential for osteoblast differentiation in both endochondral and intramembranous bones and is required for osteoblast proliferation (14-16, 27, 34).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in our study no significant variation was detected in Runx2 levels. However, our results measured an upregulation of Sp7 (Osterix), indicating OBs differentiation at early and late stage (Santo et al, 2013;Kawane et al, 2018). Sp7 is a transcriptional factor expressed in developing bones regulating the commitment of MSCs toward osteoblastic lineage (Rutkovskiy et al, 2016).…”
Section: Discussionmentioning
confidence: 55%